PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK UNTUK MENINGKATKAN HASIL BELAJAR IPS KELAS IV B SDN 015 PENYAGUAN - ', Rosminiwati; Noviana, Eddy; Kurniaman, Otang (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is motivated by teh fach is found in teh class IV B SDN 015 Penyaguan, which shows the results of lerning in  social sains is still relatively. Formulation the problem is this research is: “Does the application of Talking stick model can improve learning outcomes in social sains studen of SDN 015 Penyaguan?”.This research aims to improve learning autcomes in social sains students of SDN 015 Penyaguan with applecation of learning models Talking Stick. The hypothesis og this study is that if applied learning model Talking Stick it can improve learning outcomes in social sains students of SDN 015 Penyaguan. This study was conducted in SDN 015 Penyaguan in marech 2016. This from is research is classroom acstion research ( PTK) are planned as much as two cycle. The subjects were students of class IV B SDN 015 Penyaguan academic 2015/2016 which amounted to 26 people consisting of 12 men end 14 women. Based on the results of research of teacher activity sheet seen rising each meeting. At the firist meeting of the firist cycle of 67% ,the second meeting of the frist cycle of 71%, at the fourth meeting of the second cycle of 75%,and the fifth meeting of the second cycle of 87% .student activity observation sheet also increased at every meeting. At the first meeting of the firist cycle of 62% ,the scoond meeting of the first cycle of 67%, at the fourth meeting of the second cycle of 75% and the fifth meeting o the second cycle of 83%. Mastery learning outcomes to repeat at frist cycle increased 50,00% from the base score of 15,38% to 65,38%. In the second cycle increased by 19,23% to 84,61%.The average value in the base score 60,57, UH  then the frist cycle to 75,19 with an increase of 24,13%. Where as the second cycle of the  average  value of UH becomes 79,61 with an increase of 31,43%.So that research result are consistent with the hypothesis. Keyword: Models Talking Stick, Learning Outcame IPS